Promoting Digital Inclusion for Enhanced Resident Wellbeing: An Examination of Aged Residential Care Facility Websites - Wrapson, Wendy; Gasteiger, Chiara (New Zealand Medical Association, 2024)
Objective: Little is known about the extent to which aged care operators in Aotearoa New Zealand support and promote residents’ use of digital technologies. The aim of the study was to undertake an assessment of aged residential care (ARC) facilities’ provision of digital technology devices/internet access and digital learning opportunities for residents and to determine any COVID-19 related impact. Methods: Information on technology and internet provision from 558 ARC facilities was extracted from facilities’ own or related websites in 2019, and repeated in 2021. ARC facilities were categorised according to whether they provided: (1) digital devices, (2) internet access, (3) internet-based leisure activities, or (4) made no reference to technology. Results: In 2019 (pre-COVID-19), 392 (70%) of the 558 ARC facilities included in the study publicised availability of internet-based technologies (primarily wifi) for resident use; however, only 46 (8%) mentioned providing access to computer devices. In 2021 (during the pandemic), there had been a small increase to 421 (76%) and 54 (10%) facilities respectively. The number of facilities providing internet-based leisure activities only was 63 (11%) in 2019 and 55 (10%) in 2021. Those not mentioning technology at all had reduced from 166 (30%) in 2019 to 137 (24%) in 2021. Conclusion: The findings suggest that ARC facilities could be more proactive in enabling residents to participate in the digital world. The periods of social isolation due to COVID-19 do not appear to have had a major impact on ARC facilities’ promotion of digital technology use by residents.
Keywords: 4203 Health Services and Systems; 42 Health Sciences; Emerging Infectious Diseases; Infectious Diseases; Coronaviruses; Aging; Clinical Research; Health Services; 3 Good Health and Well Being; 11 Medical and Health Sciences; General & Internal Medicine; 32 Biomedical and clinical sciences; 42 Health sciences; Humans; COVID-19; New Zealand; Aged; SARS-CoV-2; Internet; Homes for the Aged; Pandemics; Coronavirus Infections; Pneumonia, Viral; Social Isolation; Betacoronavirus; Leisure Activities; Humans; Pneumonia, Viral; Coronavirus Infections; Social Isolation; Leisure Activities; Internet; Aged; Homes for the Aged; New Zealand; Pandemics; Betacoronavirus; COVID-19; SARS-CoV-2